Determinan Profitabilitas Bank Umum Syariah Di Indonesia Dengan Tingkat Likuiditas Sebagai Variabel Intervening - Sasabila Tisat Anisa; Saiful Anwar (JPS (Jurnal Perbankan Syariah), 2021)
This research aims to analyze the effect of capital adequacy ratio (CAR), financing risk (NPF), and operational efficiency (BOPO) on profitability (ROA) with liquidity level (FDR) as an intervening variable in Islamic commercial banks (ICB) in Indonesia in 2015 to 2019. The data used is secondary data in panel data, taken from the annual reports published by each ICB official website. Data analysis used multiple linear regression and path analysis. The results of this study found that CAR has a negative effect on ROA, NPF has a negative effect on ROA, BOPO has a negative effect on ROA, FDR has a positive effect on ROA, CAR has a negative effect on FDR, NPF has a negative effect on FDR, BOPO has a positive effect on FDR liquidity. At the same time, FDR cannot be an intervening variable in the relationship of CAR, NPF, BOPO to ROA. This research provides insight for ICB in maintaining the value of NPF and BOPO to increase the company's net profit.